Hematological Condition of Tambaqui (Colossoma macropomum) Reared in Floating Cages Placed in the Kampar River and in Pond in the Rumbio Village, Kampar Regency - Ayu Lestari Hasibuan; Iesje Lukistyowati; Morina Riauwaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This research was conducted on May to June 2017in theLaboratory of Parasite and Fish Disease of Fisheries and Marine Faculty, Riau University.This research aimed to understand the health condition of Tambaqui reared in Floating Cageculture Placed in the Kampar River and in Pond in the Rumbio Village, Kampar Regency.The method used in this research was the survey method with two different locations namely up-down stream, and in pond. fish samples were of obtained in 3 times every 10 days. The were 27 fishes, ranged from 13-16 TL. The blood was taken from the caudal vena using 1ml springe wet with 10% EDTA. Haematologycal parameters measured were blood glucose, erythrocyte, leucocyte, hematocryte and hemoglobin. Results shown that the blood glucose114mg/dL, total of erythrocytelevel 2,21x106cells/mm3, total of leucocyte 1,37x105cell/mm3, hematocryte 26,66% and hemoglobin 7,33 g/dl in floating cagesdownstream-upstreamhas a blood glucose 80,33 mg/dl, total of erythrocyte2,38x106cell/mm3, total of leucocyte1,29x105cell/mm3, hematocryte27,66% and hemoglobin 7,66 g/dl, while the fish that were rearead in the pond has a blood glucose 66mg/dl, total of erythrocyte2,37x106 cell/mm3, total of leucocyte1,27x105cell/mm3, hematocryte27,00% and hemoglobin7,66 g/dl. It can be concluded that the best result was in the fish result reared in Pond Rumbio village which was very suitable for Tambaqui fish. Key Words : Hematologycal, Colossoma macropomum, Cageculture, Pond